Domain structure of a human general transcription initiation factor, TFIIF. - Yonaha, M (1993)
The structural and functional domains of a general transcription initiation factor, TFIIF (RAP30/74, FC), have been investigated using various deletion mutants of each subunit, both in vivo and in vitro. An in vivo assay showed that the N-terminal sequence containing residues of 1-110 of RAP30 that is located close to a sigma homology region interacts with a minimum sequence of residues 62-171 of RAP74 to form a heteromeric interaction. Reconstitution of in vitro transcription activity by deletion mutants of RAP74 clearly indicated that both N-terminal residues 73-205 and C-terminal residues 356-517 are essential for full activity, the former interacting with RAP30, thus complexing with RNA polymerase II. From these data, the functional significance of domain structure of TFIIF is discussed in terms of its sigma homology sequences and complex formation with RNA polymerase II in the initiation and elongation of transcription.